Splatoon. Vol. 3 - Hinodeya, Sankichi; Haun, Jeremy; Hurley, Jason A., 1981- (Viz Media, LLC, 2018)
"Ink still fresh from their victories against the S4, Team Blue's Inklings find themselves in even more trouble! Goggles and Rider must stop an evil subterranean plot, and a new Inkling joins the team. New weapons, new foes, and new friends enter the splatfield as Team Blue prepares for its toughest challenge yet: the Square King Cup!"--pg4 of cover.